Survival outcomes of the NeoALTTO study (BIG 1–06): updated results of a randomised multicenter phase III neoadjuvant clinical trial in patients with HER2-positive primary breast cancer. (September 2019) - Huober, Jens; Holmes, Eileen; Baselga, José; de Azambuja, Evandro; Untch, Michael; Fumagalli, Debora; Sarp, Severine; Lang, Istvan; Smith, Ian; Boyle, Frances; Xu, Binghe; Lecocq, Christophe; et al.
Abstract: Background: Lapatinib (L) plus trastuzumab (T) with weekly paclitaxel significantly increased the pathologic complete response (pCR) rate compared with the anti–human epidermal growth factor receptor 2 (HER2) agent alone plus paclitaxel. The event-free survival (EFS) and overall survival (OS) by the treatment arms L + T vs. T and L vs. T and the relationship between pCR and EFS/OS both in the whole study population and according to hormone receptor–negative and hormone receptor–positive cohorts after a median follow-up of 6.7 years were assessed. Patients and methods: Four hundred fifty-five patients with HER2-positive early breast cancer randomly received L 1500 mg/day (n = 154), T (common dose, n = 149) or L 1000 mg/day plus T (n = 152) for 6 weeks, followed by the assigned anti-HER2 treatment combined with paclitaxel weekly × 12. After surgery, patients received 3 cycles of fluorouracil, epirubicin and cyclophosphamide. The primary end-point was pCR (ypT0/is; for current analysis, it is ypT0/is ypN0), and the secondary end-points were EFS and OS. Results: Six-year EFS rates were 67%, 67% and 74% with L, T and L + T, respectively (L vs T: hazard ratio [HR], 0.98 [95% confidence interval CI, 0.64–1.51; P = .93]; L + T vs T: HR, 0.81 [95% CI, 0.52–1.26; P = .35]). Six-Year OS rates were 82%, 79% and 85% for L, T and L + T, respectively (L vs T: HR, 0.85 [95% CI, 0.49–1.46; P = .56]; L + T vs T: HR, 0.72 [95% CI, 0.41–1.27; P = .26]). In landmark analyses, patients with a pCR had a significantly higher 6-year EFS (77% and 65%) and OS (89% and 77%) compared with those without a pCR for both overall and the hormone receptor–negative cohort. Conclusion: Achieving a pCR is important in HER2-positive disease and translates into better long-term outcome with regard to EFS and OS. Highlights: Achieving a pathologic complete remission is important in human epidermal growth factor receptor 2 (HER2)–positive breast cancer disease. Achieving a pathologic complete remission translates into a better long-term outcome with regard to event-free survival (EFS) and overall survival (OS). EFS and OS after 6 years did not differ significantly between the 3 treatment groups, although lapatinib + trastuzumab showed numerically higher EFS than trastuzumab in the hormone receptor–negative group.